Code Mixing in Travel Secrets Youtube Video Episode 40 - Dewi, Ni Nyoman Pipin Purnama; Utami, Ni Made Verayanti; Putri, I Gusti Ayu Vina Widiadnya (Journal of Language and Applied Linguistics, 2024)
The study concerned with the code mixing found in Travel Secrets Video YouTube Channel Episode 40. The study aims to identify the types of code mixing found on Travel Secrets Video YouTube Channel Episode 40 as well as to describe the reason of code mixing found on Travel Secrets Video YouTube Channel Episode 40. The data were taken from Travel Secrets Video YouTube Channel Episode 40 on the video “Penjelasan Boy William Dua Kali Gagal Menikah” by applying the theory types of code mixing by Hoffman (1991) and reasons of code mixing by Hoffman (1991). The analysis was done by applying descriptive qualitative and quantitative method with observation method and noted taking technique to collect the data. This study shows that there are three types of code mixing found and three reasons of code mixing found. The study concludes that intra-sentential code mixing is the most frequently used in types of code mixing and talking about particular topic is the most frequently used in reasons of code mixing. By doing code mixing, it is easier to build a sense of solidarity between the host and the guest rather than using only one language and making the conversation more attractive.